MANAJEMEN RISIKO PROYEK PENGEMBANGAN E-BISNIS (Dinamika Ekonomi, 2003)
Until recently, as businesses become more dependent on information system for theiroperations, information system managers are under increasing pressure to developquality system on time within budget, Thus, in addition to their technical skills, they mustmaster the necessdry management skills ta lead and control project management bymanaging riskfor e-bussiness development .In this article, we will explore the fundamental principles and concepts of riskmanagement for e-bisnis development project, and some of the methods to handle riskinvolved in managing a successful project. The goal is to give readers enough coverageon the topic to gain more knowledge and encourage further application in the ebussines s development.Keyword : Information System, Techincal skill, e-bussiness development project